A DIFFERENTIAL EVOLUTION ALGORITHM DEVELOPED FOR A NURSE SCHEDULING PROBLEM - Shahnazari-Shahrezaei, P; Tavakkoli-Moghaddam, R; Azarkish, M; Sadeghnejad-Barkousaraie, A (The South African Journal of Industrial Engineering, 2012)
Nurse scheduling is a type of manpower allocation problem that tries to satisfy hospital managers